Pelatihan Kader Kesehatan untuk Meningkatkan Pengetahuan Tentang Deteksi Dini Kanker Leher Rahim di Kecamatan Sawangan Magelang, Jawa Tengah - Meilani, Niken; Setiyawati, Nanik (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
One of the most common cancers among women is cervical cancer. Various sociodemographic factors such as age, socioeconomic status, and sexual activity, as well as smoking, history of sexually transmitted infections, chronic trauma, and a family history of cervical cancer, all contribute to its development. The government’s effort to prevent cervical cancer is carried out through early detection using the Visual Inspection with Acetic Acid (VIA) test, which is currently implemented in all community health centers across Indonesia. However, most women do not undergo early detection because they are unaware of the program. Health cadres are expected to serve as the frontline in communities, being responsive and attentive to local health issues, while also encouraging community participation to achieve optimal health. Training serves as a capacity-building strategy for PKK cadres. The community service program was conducted by providing information and guidance to health cadres through lectures, question-and-answer sessions, and video screenings on cervical cancer early detection. This activity took place on Friday, July 1, 2022, with 35 participants. Evaluation was conducted using pre- and post-tests. The results showed a significant increase in knowledge about cervical cancer early detection before and after the training, with a p-value of 0.001. Keywords: IVA, Papsmear, community empowerment.